Looking under the hide of animals. The history of ultrasound to assess carcass composition and meat quality in farm animals - Silva, Severiano R; Stouffer, James R (História da Ciência e Ensino: construindo interfaces, 2019)
Resumo O desafio de saber qual a composição de um animal vivo tem sido perseguido de forma incessante desde os anos 50 do século XX. Ao longo deste tempo, diversas técnicas têm sido testadas como comprovam os numerosos trabalhos científicos sobre o tema nas principais revistas de ciência animal. O objetivo central destes trabalhos é a obtenção in vivo de informação sobre características relacionadas com a carcaça e com a qualidade da carne. As técnicas que empregam ultrassons estão entre as que mais sucesso apresentam. Há ao longo da história vários marcos que são pilares no desenvolvimento dos ultrassons. No século XVIII, o padre e biólogo Lazzaro Spallanzani, intrigado com a capacidade de orientação noturna dos morcegos, descobriu a ecolocalização. Em 1880, os irmãos Curie apresentaram as propriedades piezelétricas de determinados cristais. Mais tarde durante e entre as duas grandes guerras mundiais ocorreram inúmeros desenvolvimentos tecnológicos no campo militar, mas também no campo médico relacionados com ultrassons. Durante a década de 50 foram apresentadas utilizações de ultrassons com imagem. Quase simultaneamente a primeira utilização em animais foi realizada em 1956 nos EUA. Desde então ocorreram enormes desenvolvimentos quer nos equipamentos de ultrassons, quer nas imagens e na sua análise. Atualmente os ultrassons são uma ferramenta precisa e objetiva que apresenta um papel relevante para avaliar in vivo características da carcaça e de qualidade da carne de ovinos, suínos e bovinos. Palavras-chave: história, ultrassons, ciência animal, carcaça, qualidade da carne Abstract The challenge of knowing the composition of a living animal has been pursued incessantly since the 1950s. Throughout this time, several techniques have been tested as evidenced by the numerous scientific articles found on the subject in the leading animal science journals. The primary objective of this work is obtaining information in vivo on characteristics related to carcass and meat quality. The techniques that employ ultrasound are among the most successful. Throughout history, several milestones have been found in the development of ultrasound. In the eighteenth century, priest and biologist Lazzaro Spallanzani, intrigued by the nocturnal ability of bats, discovered echolocation. In 1880 the Curie brothers presented the piezoelectric properties of certain crystals. Later during and between the two world wars, numerous ultrasound technological developments occurred in the military field but also the medical field. Ultrasound with imaging was presented during the 1950s. The application of ultrasound to animals has had a very close relationship to medical applications, and almost simultaneously the first use in animals was held in 1956 in the USA. Since then, there have been enormous developments in both the ultrasound equipment and the images and their analysis. Ultrasound is currently an accurate and objective tool that has a relevant role in evaluating in vivo carcass characteristics and meat quality in the main farm species (cattle, swine, goat, sheep and poultry) and fish. Keywords: history, ultrasound, animal science, carcass, meat